Public preferences toward shopping mall interior landscape design in Kuala Lumpur, Malaysia - Hami, Ahmad; Fazle Moula, Fazilah; Maulan, Suhardi (Elsevier, 2018)
The number of malls in Malaysia has not only increased dramatically, but they have also been subject to continual expansion over the past few years. Despite this rate of expansion, there has not been enough attention paid to the quality of the spaces and interior landscaping of the malls on the basis of people’s preferences. This study aimed to bring out people’s preferences towards interior public spaces at shopping malls. Using a photo questionnaire, the results pointed to three major dimensions: the green dimension, the seating dimension, and the business dimension in open spaces of shopping malls where the green dimension received the highest preference. The green dimension includes water features, trees, plants, and shrubs. Moreover, legibility and coherence affected people’s preferences for open spaces in shopping malls. People did not prefer the business dimension to spending leisure times, involving business equipment in shopping malls. The study suggested that shopping malls should be designed as truly public spaces with ample public areas. Green elements and water features should be used more in shopping mall public places. Moreover, policy makers can expand the “shopping town” approach for people’s leisure in malls that should include characteristics such as rivers or waterfalls with a dynamic water flow, famous places, public libraries, gardens, town activities, and cultural activities.